Performance of Ocean Thermal Energy Conversion Closed Rankine Cycle Using Different Working Fluids - N., Samsuri; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; M. N. M., Razali (IOP Publishing, 2021)
Ocean Thermal Energy Conversion (OTEC) is a foundation for an appealing renewable energy technology regarding its vast and inexhaustible resources of energy, renewability, stability, and sustainable output. The principle of an OTEC power plant is to exploit the energy accumulated in between the top layer of warm surface seawater (heat source), and the cold layer of deep seawater (heat sink). The plant operates based on a Rankine cycle to produce electricity between the source and the sink at the smallest temperature difference of approximately 20 K. In an OTEC power plant, a commonly utilized working fluid is ammonia since its qualities are suitable for the OTEC cycle. Nevertheless, ammonia poses certain potentially lethal health risks and hazardous fluid. Hence, the effect of the working fluid types, and the subsequent operation conditions may be critical and therefore become the subject of this study. The analysed working fluids, including that of ammonia, are ammonia-water mixture (0.9), propane, and refrigerants (R22, R32, R134a, R143a, and R410a). The results revealed that ammonia-water mixture showed the highest network performance and reliability. Even so, it is essential to continue seeking the suitable working fluids which are safe and economically effective to replace ammonia.